Moral Legitimacy of Indonesia's Free Nutritious Meal Program through Pluralistic Ethical Perspectives - Alie Zainal Abidin; Indra Lukmana Putra; Mochamad Valri Veriandy (University of Merdeka Malang, 2026)
The Food for Health Program (MBG) is an Indonesian government strategic program that focuses on improving public health through the promotion of nutritional practices to boost human quality. The program raises the important question of morality, in terms of issues such as moral rights, the distribution of benefits, policy priorities, and the use of the public’s wealth. Evaluating the MBG program in this new light calls for a different kind of approach, based on a review of the basic moral grounds for the use of state power. This study uses three main ethical points of reference deontology, natural law, and the utilitarian point of reference to assess the MBG program’s foundation. The purposes of this study are to evaluate the moral legitimacy of the MBG program by using a comparative analysis of deontological, teleological, and utilitarian perspectives. To be specific, this study reviews how the three philosophical approaches interpret the state’s moral obligations, long-term development goals, and commitment to public welfare in terms of evaluating the programs’ fairness and legitimacy. This study adopts a normative-analytical method based on philosophical analysis. We critically reviewed policy documents, ethical principles, and relevant literature to identify the normative foundations of the MBG program. Several strands of thinking in public policy have different and yet also similar ways of looking at the MBG program. Looking at it from a view of what is good, the program is based on the idea that the government has a right to protect the basic rights of people, as well as the rights to food and nutrition, no matter what happens as a result of the policy. utilitarianism evaluates the program as a result of its success in creating the greatest good for the greatest number, while also bringing to light other problems such as low costs and costs of doing nothing that might lower the social benefits overall. The other view, called teleology, looks at the program based on its impact on things like overall human progress, making sure everyone gets a fair deal, and making sure people are doing well. Taken together, this suggests that while each of these three ethical points of view is useful in its own right, they are in fact best viewed as working together to help us understand the moral basis for the MBG program’s claim to morality. This study makes a positive impact on the study of public policy by proposing a model for evaluating the MBG program that includes moral commitments, policy impacts, and goals for growth in the future. The MBG program's valid moral standing not only comes from protecting public rights but also from fair implementation, making good use of money, and making sure the public is doing well over the years. This analysis will serve as a useful point of reference for governments in their efforts to make sure their policies are fair and right.